An improved hybrid particle scheme for hypersonic rarefied-continuum flow. (February 2016) - Jiang, Tingting; Xia, Chenchao; Chen, Weifang
Abstract: An improved hybrid particle simulation method (IHPSM) intended for hypersonic flows including various Knudsen number regimes is developed. In this approach, two different types of particle simulation methods, the direct simulation Monte Carlo (DSMC) method and the DSMC-based equilibrium particle simulation method (EPSM), are adopted to simulate the particle movement and collision in non-equilibrium regions and equilibrium regions respectively. We first present the design of equilibrium breakdown parameters to classify the cells into two different simulation regions. Then based on the information of the collision frequency and the maximum particle velocity in the cell, we further propose and employ a novel adaptive local time step method to increase the simulation efficiency. Finally, we verify the developed hybrid particle scheme through two representative test cases involving the hypersonic flows over a hollow cylinder-flare and a sphere. The IHPSM results show excellent agreement on flow field and surface properties with those obtained from the literature. Notably, the IHPSM method is able to decrease the simulation expense by about 55% compared with DSMC in the sphere test. Highlights: An improved hybrid particle scheme for rarefied-continuum flow is proposed. The adaptive local time step method can improve the simulation efficiency. IHPSM obtains a 55% reduction in computational cost compared with DSMC.